University spillovers, absorptive capacities, and firm performance - Erik E. Lehmann; Matthias Menter; Katharine Wirsching (Eurasian Business Review, 2022)
This study investigates the impact of both university spillovers and firms' absorptive capacities on firms' financial performance, using a multilevel approach. Considering internal firm characteristics as well as external regional characteristics, our results clearly show that university spillovers do not have a per se stimulating effect. It is the interaction between firms' absorptive capacities and local university spillovers, which proves to have a positive and significant effect on firms' economic performance. We further find that there is an optimal level of absorptive capacities, implying that 'a more the better' logic does not apply. Our findings give impetus to a call for more comprehensive public policy strategies. Policy makers have to balance the support provided to knowledge producing regional actors such as universities as well as knowledge exploiting actors such as knowledge-based firms to leverage local resources and ultimately create economic value within regional innovation systems by enabling efficient technology transfer processes.
Keywords: O31; O32; O38; 650; Regional innovation systems; Absorptive capacity; Knowledge spillover; University spillover; Technology transfer; Firm performance